2022
DOI: 10.1177/07482337221136949
|View full text |Cite
|
Sign up to set email alerts
|

Altered M1/M2 polarization of alveolar macrophages is involved in the pathological responses of acute silicosis in rats in vivo

Abstract: Alveolar macrophages play a vital role in the development of acute silicosis, but the dynamic changes of M1 and/or M2 phenotypes have not been elucidated. In this study, acute silicosis models of rat were established by a one-time dusting method, and the rats were sacrificed after 1, 3, 7, 14, and 28 days. The polarity states of macrophages were assessed by measuring the M1/M2 marker genes of alveolar macrophages and the M1/M2 marker proteins in bronchoalveolar lavage fluid. The pathological changes of lung ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It is noteworthy that IFN-γ is thought to polarize M1ϕ, causing up-regulation of inflammatory cytokines upon viral infection whilst inhibiting growth and enhancing apoptosis of lung cells in vitro [ 233 ]. Dysregulation of AMϕ polarity therefore needs to be considered in context with other in vitro or in vivo respiratory research where both fibrosis and inflammation can occur (e.g., silicosis) [ 234 ]. M1ϕ and M2ϕ, along with gene protein markers within bronchoalveolar lavage fluid (BALF), are one way of ascertaining polarity state alterations associated with disease.…”
Section: Inflammatory Cells and Phagocytesmentioning
confidence: 99%
“…It is noteworthy that IFN-γ is thought to polarize M1ϕ, causing up-regulation of inflammatory cytokines upon viral infection whilst inhibiting growth and enhancing apoptosis of lung cells in vitro [ 233 ]. Dysregulation of AMϕ polarity therefore needs to be considered in context with other in vitro or in vivo respiratory research where both fibrosis and inflammation can occur (e.g., silicosis) [ 234 ]. M1ϕ and M2ϕ, along with gene protein markers within bronchoalveolar lavage fluid (BALF), are one way of ascertaining polarity state alterations associated with disease.…”
Section: Inflammatory Cells and Phagocytesmentioning
confidence: 99%
“…They are distinct by ability to induce and inhibit inflammatory responses on exposure to pathogens and cell surface markers [177]. [177] Dysregulation of AM polarity is pivotal in the pathogenesis of respiratory diseases such as silicosis [191]. The AM/M1/M2 gene markers and protein markers within bronchoalveolar lavage fluid (BALF) can be used to assess polarity state alterations associated with diseases.…”
Section: Iii)macrophage Introductionmentioning
confidence: 99%
“…Studies have reported that M1 macrophages are consistent with pro-inflammatory responses, pathogen resistance and their polarity is prioritized during early stages of disease. Antagonistic M2 cells typically occur at sites where anti-inflammatory microbial effects occur, tissue remodeling is required, and their polarity is greater emphasized as time from disease onset increases [191]. A hybrid M1/M2 phenotype that incorporates both subtypes combined functions has been theorized to exist and allows for rapid switching between desired functions appropriate in response to presenting stimuli and changes within healthy mucosal tissue environments [192].…”
Section: Iii)macrophage Introductionmentioning
confidence: 99%
“…They are distinct by ability to induce and inhibit inflammatory responses on exposure to pathogens and cell surface markers [174]. [174] Dysregulation of AM polarity is pivotal in the pathogenesis of respiratory diseases such as silicosis [188]. The AM/M1/M2 gene markers and protein markers within bronchoalveolar lavage fluid (BALF) can be used to assess polarity state alterations associated with diseases.…”
Section: Iii)macrophage Introductionmentioning
confidence: 99%
“…M1 Mϕ are consistent with pro-inflammatory responses, pathogen resistance and their polarity is prioritized during early stages of disease. Antagonistic M2 cells typically occur at sites where anti-inflammatory microbial effects occur, tissue remodeling is required around epithelial cell layers [188]. A hybrid M1/M2 phenotype allows for rapid switching between desired functions appropriate in response to presenting stimuli and changes within healthy mucosal tissue environments [189].…”
Section: Iii)macrophage Introductionmentioning
confidence: 99%